2021
DOI: 10.3390/ijerph182413227
|View full text |Cite
|
Sign up to set email alerts
|

Polish Pharmacy Students’ Readiness, Qualifications, Competences, Relevance, Motivation and Effectiveness to Promote Health in Community Pharmacies

Abstract: Background: One of the parts of the broadly understood pharmaceutical care is health promotion. Therefore, the study aimed to find out how pharmacy students in Poland assess their own readiness to promote health in pharmacies and their own qualifications, competences, relevance, motivation and effectiveness of health promotion in pharmacies. Methods: The study conducted in 2019 comprised 206 pharmacy students from Poland. The authors’ survey questionnaire had two parts: Readiness to promote health in pharmacie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In turn, in our study, the availability of health education in general and its availability in the field of disease prevention conducted by pharmacists, as well as the communicativeness of health education conducted by pharmacists for the patient with regards to help in dealing with health problems, were assessed significantly better by the respondents with primary education than other respondents. Our previous studies analyzed how pharmacy staff and pharmacy students in Poland evaluated their own qualifications, competencies, relevance, motivation, and effectiveness of health promotion [ 38 , 39 ]. The relevance of health promotion was rated by the pharmacy staff at a level of 7.0 ± 1.7, in the pharmacy students the relevance was rated at a higher level of 7.4 ± 1.8 while in the present study in patients at post-working age, the relevance was rated at a lower level of 5.8 ± 2.8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, in our study, the availability of health education in general and its availability in the field of disease prevention conducted by pharmacists, as well as the communicativeness of health education conducted by pharmacists for the patient with regards to help in dealing with health problems, were assessed significantly better by the respondents with primary education than other respondents. Our previous studies analyzed how pharmacy staff and pharmacy students in Poland evaluated their own qualifications, competencies, relevance, motivation, and effectiveness of health promotion [ 38 , 39 ]. The relevance of health promotion was rated by the pharmacy staff at a level of 7.0 ± 1.7, in the pharmacy students the relevance was rated at a higher level of 7.4 ± 1.8 while in the present study in patients at post-working age, the relevance was rated at a lower level of 5.8 ± 2.8.…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of health promotion was rated by the pharmacy staff at a level of 7.0 ± 1.7, in the pharmacy students the relevance was rated at a higher level of 7.4 ± 1.8 while in the present study in patients at post-working age, the relevance was rated at a lower level of 5.8 ± 2.8. Similarly, the effectiveness of health promotion was rated at the highest level by pharmacy students (6.4 ± 1.8) compared to pharmacy staff (5.7 ± 1.9) and people at post-working age (4.6 ± 2.7) [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study distinguished aspects of readiness to promote health in pharmacies at the level of pharmacy students, pharmacy employees, and individual self-belief. The results showed that students negatively assessed the readiness of pharmacy students and pharmacists to provide such a service, although individually, they believed that they were ready to promote health in their future work [ 22 ]. Most importantly, despite the indicated limitations in systemic solutions that hinder the promotion of health in pharmacies, in term of running a PC, students in our study showed high motivation to provide such a service.…”
Section: Discussionmentioning
confidence: 99%